2016
DOI: 10.1186/s12884-016-0867-2
|View full text |Cite
|
Sign up to set email alerts
|

Stressful events, social health issues and psychological distress in Aboriginal women having a baby in South Australia: implications for antenatal care

Abstract: BackgroundAround 6 % of births in Australia are to Aboriginal and Torres Strait Islander families. Aboriginal and Torres Strait Islander women are 2–3 times more likely to experience adverse maternal and perinatal outcomes than non-Aboriginal women in Australia.MethodsPopulation-based study of mothers of Aboriginal babies born in South Australia, July 2011 to June 2013.Mothers completed a structured questionnaire at a mean of 7 months postpartum. The questionnaire included measures of stressful events and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Regrettably, Indigenous mothers are more likely to attend their first antenatal visit later in the pregnancy, and these visits are less frequent than that of non-Indigenous pregnant women [ 23 , 24 ]. The literature also reports a trend of underutilisation of preventive health services, including dental services [ 25 , 26 ]. While financial cost is a main barrier to health service utilisation for this population [ 27 ], underlying social and historical factors continue to contribute to their distrust of healthcare professionals and the health system [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, Indigenous mothers are more likely to attend their first antenatal visit later in the pregnancy, and these visits are less frequent than that of non-Indigenous pregnant women [ 23 , 24 ]. The literature also reports a trend of underutilisation of preventive health services, including dental services [ 25 , 26 ]. While financial cost is a main barrier to health service utilisation for this population [ 27 ], underlying social and historical factors continue to contribute to their distrust of healthcare professionals and the health system [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…She proposed that disadvantaged groups experience earlier deterioration of health, resulting from cumulative exposures to social adversity coupled with negative coping behaviors. It is well documented that Australia's Indigenous populations experience disadvantage across a range of health, social, and economic indicators, with very high levels of social issues during pregnancy, including family violence, poverty, and housing instability . In our study, we observed that coping behaviors such as smoking and alcohol increased with age, contributing to a higher risk profile during women's peak reproductive years.…”
Section: Discussionmentioning
confidence: 46%
“…It is well documented that Australia's Indigenous populations experience disadvantage across a range of health, social, and economic indicators, 30 with very high levels of social issues during pregnancy, including family violence, poverty, and housing instability. 31 In our study, we observed that coping behaviors such as smoking and alcohol increased with age, contributing to a higher risk profile during women's peak reproductive years. Furthermore, detailed assessment of the risks of poor perinatal outcomes among Indigenous women across the full spectrum of age groups (including 35+ years) would be a fruitful area for future research.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Strategies that work for particular communities and contexts may not work in others. In the Australian setting, this is most evident in relation to First Nations people, who experience markedly worse perinatal mental health outcomes than non‐Indigenous Australians 8 .…”
mentioning
confidence: 99%